Justice and nature of contract as determinant of abandoned housing project - Abdullah, Moha Asri; Abdul Razak, Dzuljastri; Mohamed, Mustafa Omar; Olaniyi, Oladokun Nafiu (2015)
This study aims at exploring the perception of stakeholders particularly the home buyers about the causes of abandoned housing project (AHP) in Malaysia. Assessing the determinant of AHP could assist in mitigating the effect of AHP in Malaysia. In this study, we employed factor analysis and Structural Equation Modelling (SEM) to achieve the stated objective. The total sample size of the study comprises of 328 respondents that cut across all states in Malaysia. Two main constructs namely justice and nature of contract are considered in this study. The result of the SEM revealed that lack of justice and weak regulatory system couple with the nature of the contract of financing significantly contributes to the problem of abandoned housing projects. Hence, it is suggested that fairness in contract (e.g. risk sharing) and sound regulatory system could help in mitigating the effect of abandoned housing problems.